2020
DOI: 10.1002/csr.1945
|View full text |Cite
|
Sign up to set email alerts
|

The role of women on boards in corporate environmental strategy and financial performance: A global outlook

Abstract: This study examines the impact of board gender diversity on corporate environmental strategy and financial performance. Based on 12 corporate environmental policies in 3389 firms worldwide, we identified four types of corporate environmental strategies by using the latent class regression model: an inactive strategy, a reactive strategy, a pollution prevention strategy and a sustainable development strategy. The empirical evidence shows that women on boards contribute to the promotion of proactive environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 69 publications
1
56
0
Order By: Relevance
“…Multiple studies have shown that board gender diversity plays an essential role in a company's environmental performance [50,73]. These studies are based on differences in behaviour between men and women.…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that board gender diversity plays an essential role in a company's environmental performance [50,73]. These studies are based on differences in behaviour between men and women.…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
“…This relationship has been confirmed for samples from various countries and regions. Specifically, studies have been conducted in the United States [26,42,43,50,64,83], France [47], the United Kingdom [25], China [86], Australia [85], Europe [27,77,88] and globally [44,73,96].…”
Section: Board Gender Diversity and Environmental Performancementioning
confidence: 99%
“…Shafiei and Maleksaeidi [68] confirmed the study's stated findings and concluded that females are more environmentally friendly than males. Xie et al [69] concluded that women as corporative board members are always keen to propose environmentally friendly policies to go-for carbon mitigating strategies. Islam and Managi [70] stressed the need to spread environmental knowledge to improve pro-environmental behavior in the commodity resource market worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, some empirical studies find no relationship (Glass, Cook, & Ingersoll, 2016; Post, Rahman, & Rubow, 2011; Walls, Berrone, & Phan, 2012). However, most studies demonstrate the positive influence of women on CSR performance (Xie, Nozawa, & Managi, 2020; Aslam, Abdul, Makki, Mahmood, & Amin, 2018; Charumathi & Rahman, 2019; Isidro & Sobral, 2015; Liao, Zhang, & Wang, 2019; Manita, Bruna, Dang, & Houanti, 2018; Setó‐Pamies, 2015; Valls Martínez et al, 2019; Zhang, Zhu, & Ding, 2013).…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%